Altered metabolites of the rat hippocampus after mild and moderate traumatic brain injury – a combined in vivo and in vitro1H–MRS study. (31st July 2017) - Singh, Kavita; Trivedi, Richa; Verma, Ajay; D'souza, Maria M.; Koundal, Sunil; Rana, Poonam; Baishya, Bikash; Khushu, Subash
Abstract : Traumatic brain injury (TBI) has been shown to affect hippocampus‐associated learning, memory and higher cognitive functions, which may be a consequence of metabolic alterations. Hippocampus‐associated disorders may vary depending on the severity of injury [mild TBI (miTBI) and moderate TBI (moTBI)] and time since injury. The underlying hippocampal metabolic irregularities may provide an insight into the pathological process following TBI. In this study, in vivo and in vitro proton magnetic resonance spectroscopy ( 1 H–MRS) data were acquired from the hippocampus region of controls and TBI groups (miTBI and moTBI) at D0 (pre‐injury), 4 h, Day 1 and Day 5 post‐injury (PI). In vitro MRS results indicated trauma‐induced changes in both miTBI and moTBI; however, in vivo MRS showed metabolic alterations in moTBI only. miTBI and moTBI showed elevated levels of osmolytes indicating injury‐induced edema. Altered levels of citric acid cycle intermediates, glutamine/glutamate and amino acid metabolism indicated injury‐induced aberrant bioenergetics, excitotoxicity and oxidative stress. An overall similar pattern of pathological process was observed in both miTBI and moTBI, with the distinction of depleted N ‐acetylaspartate levels (indicating neuronal loss) at 4 h and Day 1 and enhanced lactate production (indicating heightened energy depletion leading to the commencement of the anaerobic pathway) at Day 5 in moTBI. To the best of our knowledge, this is the first study to investigate the hippocampus metabolic profile in miTBI and moTBI simultaneously using in vivo and in vitro MRS. Abstract : A similar pattern of post‐traumatic brain injury (TBI) pathology was observed in both mild (miTBI) and moderate (moTBI) TBI, with the distinction of depleted N ‐acetylaspartate levels (indicating neuronal loss) at 4 h and Day 1 and enhanced lactate production (indicating heightened energy depletion leading to commencement of the anaerobic pathway) at Day 5 in moTBI post‐injury. This is the first study to investigate hippocampus metabolic profiles in miTBI and moTBI simultaneously using in vivo and in vitro magnetic resonance spectroscopy (MRS).